Cooperative norm setting on the internet. Conditions of participation from an action-theoretical perspective - Tranow, Ulf (Momentum Quarterly, 2014)
The internet offers the opportunity to involve a large number of people in collective decisions on binding rules. Procedures of ‘internet-mediated cooperative norm setting’ (ICN) provide the chance to arrive at more democratic, ‘better‘, and more legitimate decisions in both organizations and fields of politics. However, practical applications of online participation show that individuals’ willingness to participate cannot be taken for granted. The objective of this paper is to analyze the basic structure of this participation problem from an action-theoretical perspective. My initial hypothesis is that ICN is subject to a collective good problem. Successful ICN relies on the premise that persons are motivated to participate although their behavior is insignificant. Referring to the Theory of Social Rationality (Lindenberg 2001) and considering additional empirical evidence, three types of participation motives are identified which might help to overcome the collective good problem: expressive, demonstrative, and norm-orientated participation motives. These three types of motives underlie special constitutive conditions and restrictions which are discussed as well.